Bộ tập quán quốc tế về L/C,ICC-Phòng thương mại quốc tế - Đinh Xuân Trình
Bộ tập quán quốc tế về L/C : ICC-Phòng thương mại quốc tế / Đinh Xuân Trình .- H. : Đại học kinh tế quốc dân , 2009 .- 295tr. ; 24 cm